Applying the Education for Sustainable Development Approach to Energy Instruction Design for Encouraging Scientific Literacy of Junior High School Students - Dieni, Wahyu Eka Fath; Hernani, Hernani; Kaniawati, Ida (FKIP Universitas Lampung, 2022)
The purpose of this research is to produce learning designs on energy materials with the Educational for Sustainable Development (ESD) approach to develop scientific literacy that is validated and tested on a limited scale. This research uses Design and Development Research model, which uses 6 stages of the D&D model, namely 1) Identify the problems motivating the research; 2) Describe the objectives; 3) Design and develop the artifact; 4) Subject the artifact to testing; 5) Evaluating test results; and 6) Communicating test results. Interview guidelines, lesson plans, validation sheets, and worksheets are the main instruments in this research. The results are indicators derived from content standards can be found with ESD elements, and the learning design developed is considered feasible to be applied in learning. The principle in implementing ESD elements in learning is student-oriented, making the environment a source of learning and connecting local and global issues. Keywords: education for sustainable development, scientific learning, learning design DOI: http://dx.doi.org/10.23960/jpmipa/v23i2.pp670-680